Characterization of UGT716A1 as a Multi-substrate UDP:Flavonoid Glucosyltransferase Gene in Ginkgo biloba - Su, Xiaojia; Shen, Guoan; Di, Shaokang; Dixon, Richard A.; Pang, Yongzhen (Frontiers in Plant Science, 2017)
Ginkgo biloba L., a “living fossil” and medicinal plant, is a well-known rich source of bioactive flavonoids. The molecular mechanism underlying the biosynthesis of flavonoid glucosides, the predominant flavonoids in G. biloba, remains unclear. To better understand flavonoid glucosylation in G. biloba, we generated a transcriptomic dataset of G. biloba leaf tissue by high-throughput RNA sequencing. We identified twenty-five putative UDP-glycosyltransferase (UGT) unigenes that are potentially involved in the flavonoid glycosylation. Among them, we successfully isolated and expressed eight UGT genes in Escherichia coli, and found that recombinant UGT716A1 protein was active toward broad range of flavonoid/phenylpropanoid substrates. In particular, we discovered the first recombinant UGT protein, UGT716A1 from G. biloba, possessing unique activity toward flavanol gallates that have been extensively documented to have significant bioactivity relating to human health. UGT716A1 expression level paralleled the flavonoid distribution pattern in G. biloba. Ectopic over-expression of UGT716A1 in Arabidopsis thaliana led to increased accumulation of several flavonol glucosides. Identification and comparison of the in vitro enzymatic activity of UGT716A1 homologs revealed a UGT from the primitive land species Physcomitrella patens also showed broader substrate spectrum than those from higher plants A. thaliana, Vitis vinifera and Medicago truncatula. The characterization of UGT716A1 from G. biloba bridges a gap in the evolutionary history of UGTs in gymnosperms. We also discuss the implication of UGT716A1 for biosynthesis, evolution and bioengineering of diverse glucosylated flavonoids.